Creativity as the Basis of Pedagogical Innovation in Technological Education - Liubarska, Lyudmila (Educological discourse, 2025)
The article reveals the essence of creativity as one of the key factors of professional success of future teachers of technology. Theoretical analysis of modern scientific approaches allowed to outline the four-component structure of creativity: cognitive, emotional-motivational, practical-activity and productive components. An empirical study conducted among students of a pedagogical university and young teachers showed the prevalence of medium and high levels of self-esteem of creative potential. The high readiness of respondents to implement innovative methods and adapt to changes in professional activity was recorded. A direct relationship between self-confidence and the ability to creative pedagogical activity was revealed. The results of the study emphasize the importance of creating a pedagogical environment that promotes the development of creative abilities. Directions for improving the professional training of future teachers of technology through the integration of creativity components into the content and forms of educational activity are proposed. The need for further interregional research is substantiated to clarify the influence of the socio-cultural environment on the development of teachers’ creative potential.